2006
DOI: 10.1007/s00210-006-0062-5
|View full text |Cite
|
Sign up to set email alerts
|

The comparative study of Sprague–Dawley and Lewis rats in adjuvant-induced arthritis

Abstract: The outbred Sprague-Dawley (SD) rats, similar to the inbred Lewis (LEW) rats, have been recently demonstrated to be highly susceptible to adjuvant-induced arthritis (AIA). We herein compared AIA in SD and LEW rats in terms of clinical, histological, radiological, and immuno-inflammatory features. The results showed that, following inoculation with a ground Mycobacterium tuberculosis (MT) suspension, SD and LEW rats manifested closely similar disease progression, with 100% incidence and similar severity. The de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 28 publications
1
42
0
1
Order By: Relevance
“…Indeed, Cyt are key mediators of CFA-induced arthritis. Their concentration and expression are significantly elevated in serum (26) and joint tissues (present results) of CFA-injected rats, respectively, and IL-1 antagonists and TNF-α-neutralizing antibodies reduce disease severity in these animals (51,52). We propose that PRL protects against CFA-induced inflammatory arthritis by reducing Cyt levels and counteracting their proapoptotic and proinflammatory actions on synovial cells, cartilage, and bone.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Indeed, Cyt are key mediators of CFA-induced arthritis. Their concentration and expression are significantly elevated in serum (26) and joint tissues (present results) of CFA-injected rats, respectively, and IL-1 antagonists and TNF-α-neutralizing antibodies reduce disease severity in these animals (51,52). We propose that PRL protects against CFA-induced inflammatory arthritis by reducing Cyt levels and counteracting their proapoptotic and proinflammatory actions on synovial cells, cartilage, and bone.…”
Section: Discussionsupporting
confidence: 51%
“…This model is well documented for the induction of inflammation within joint tissues and for having cartilage and bone destruction similar to that in RA (26,51). Consistent with a previous study (52), we found that CFA-induced arthritis enhances the expression of apoptotic mediators in joints and showed for the first time that apoptosis occurs in large numbers of articular chondrocytes.…”
Section: Discussionmentioning
confidence: 94%
“…Though conventional treatment with steroids, NSAIDs and biological agents such as TNF-, IL-1 antagonist can control the symptoms of acute arthritis, it is ineffective in chronic inflammation and prolonged use of those agents cause various side effects (Chandrasekaran et al, 2002). Research suggests that the use of complementary and alternative medicine, primarily herbal therapies, is a positive to treat arthritis (Cai et al, 2005). Therefore, the importance of antioxidants derived from plant origin has been increased greatly in recent years (Gülçin et al, 2004;Elmastaş et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…CFA-induced polyarthritis is associated with an immune-mediated inflammatory reaction, and the rat is unique in developing polyarthritis after CFA treatment (Cai et al, 2006). The initial reaction of edema and softtissue thickening at the depot site in this model is caused by the irritant effect of the adjuvant, whereas the latephase arthritis and flare in the injected foot are presumed to be immunologic events (Ward & Cloud, 1965).…”
Section: Chan Pit Foong and Roslida Abdul Hamidmentioning
confidence: 99%